A quick-drying wear-resistant refractory castable composition and preparation method thereof

A quick-drying, wear-resistant refractory castable composition addresses rapid drying and wear resistance challenges by using a specific formulation and preparation method, ensuring high-temperature performance and structural integrity in demanding applications.

CN119039025BActive Publication Date: 2025-01-03SHANDONG LUMING NEW MATERIALS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411555033.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-03
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

Existing refractory castables face challenges in achieving rapid drying and wear resistance while maintaining high-temperature performance and structural integrity, particularly in demanding applications such as iron ditch and steel ladle linings.

Method used

A quick-drying wear-resistant refractory castable composition comprising sol binder, pH stabilizer, hardener, dispersant, and aggregate, prepared through a specific method involving pH adjustment, filtration, and high-temperature calcination of matrix fine powders, enhances drying speed and wear resistance.

Benefits of technology

The composition achieves rapid drying, improved high-temperature performance, and enhanced wear resistance, reducing the risk of matrix bursting and extending service life, with a simple and cost-effective preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119039025B_ABST
    Figure CN119039025B_ABST
Patent Text Reader

Abstract

The invention discloses a quick-drying wear-resistant refractory castable composition and a preparation method thereof, and belongs to the field of refractory materials. The castable composition comprises a sol binder, a pH stabilizer, a hardener, a matrix fine powder, a dispersant and an aggregate. The castable composition has the characteristics of short curing time, good wear resistance, high use temperature and the like; at the same time, it also has good fluidity, simple and convenient construction, and can effectively reduce heat loss, improve thermal efficiency, reduce energy consumption, and save energy and reduce emissions during application. In addition, the raw materials used in the quick-drying wear-resistant refractory castable composition are non-toxic and non-corrosive, have the characteristics of energy saving and environmental protection, and play an important role in improving and protecting the environment. At the same time, various raw materials used in the present invention can be purchased from the market, which reduces the production cost of lightweight thermal insulation refractory castables.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of refractory materials, and particularly relates to a quick-drying wear-resistant refractory castable composition and a preparation method thereof. Background Art

[0002] After years of development and evolution, monolithic refractory materials have become a widely used type of refractory materials with good performance and economic benefits. Among them, refractory castables are used in many demanding occasions due to their excellent high-temperature performance. In many cases, the market share of monolithic refractory materials has exceeded that of shaped refractory products. Refractory castables are a new type of refractory materials that have good fluidity after adding water and stirring without calcination. They are an important variety of monolithic refractory materials.

[0003] With the increase in the proportion of amorphous refractories in refractory materials, refractory castables will surely develop rapidly. At the same time, the variety will increase and the quality will also be improved accordingly. The focus will still be on the development of low-cement, ultra-low-cement and cement-free refractory castables. According to resource conditions, homogenized and high-quality raw materials and special aggregates will be selected to improve the basic composition. The use of fiber-reinforced refractory castables and self-flowing refractory castables will be studied and promoted. Various admixtures will be applied to improve the performance of refractory castables. In addition, special castables (such as iron ditch, steel ladle lining, etc.) and materials with special functions (such as wear resistance, acid resistance, alkali resistance, high-strength heat insulation, high strength and high thermal conductivity, etc.) will be developed, and production equipment and construction supporting machinery and tools will be improved in terms of production and application technology. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a quick-drying wear-resistant refractory castable composition; another purpose of the present invention is to provide a method for preparing a quick-drying wear-resistant refractory castable composition.

[0005] Technical solution: A quick-drying wear-resistant refractory castable composition, which comprises the following components mixed by weight:

[0006] 15-25 parts of sol binder, 0.5-1.5 parts of pH stabilizer, 1-2 parts of hardener, 15-25 parts of matrix fine powder, 2-3 parts of dispersant and 60-70 parts of aggregate;

[0007] Preferably, the sol binder is a small-particle silica sol, and the preparation method is as follows: add 0.3 times the volume of strong acid cation exchange resin to 19.6 degrees Baume water glass, mechanically stir for 10 minutes, filter, the filtered strong acid cation exchange resin is again stirred and washed for 5 minutes with 0.5 times the volume of water glass, filtered, the two filtrates are combined, 0.1 times the volume of water glass is added with weak alkaline anion exchange resin and stirred for 10 minutes, filtered, the filtered weak alkaline anion exchange resin is slurried and stirred with 0.2 times the volume of water glass, filtered, all filtrates are combined, and the attached sample is prepared according to the experiment on the influence of pH value on the gel time of silica sol. Figure 2 Related data, adjust pH to 9-10 with 4M sodium hydroxide aqueous solution, concentrate the solution at 80℃ under reduced pressure to 1 / 4 of the original volume, add hexadecyltrimethylammonium nitrate at 1 / 50 of the weight of water glass and nano magnesium oxide at 1 / 200 of the weight of water glass under stirring, and stir to obtain the gel. See the attached schematic diagram Figure 1 .

[0008] Preferably, the pH stabilizer is active zinc oxide powder, and the particle size of the active zinc oxide powder is 10-30 nm.

[0009] Preferably, the hardener is magnesium oxide powder, and the particle size of the magnesium oxide powder is 1-5 mm.

[0010] Preferably, the matrix fine powder is a self-made calcium dodecaaluminate nano powder, and the preparation method of the self-made calcium dodecaaluminate nano powder is: dissolving a mixed powder with a molar ratio of calcium carbonate:aluminum chloride of 12:7 in 40°C water with a stirring amount of 20 times the weight of the mixture, adding ammonia water after the solution is clear to adjust the pH to 11-12, naturally cooling and precipitating for 24 hours, filtering, and calcining at a high temperature of 1500°C for 2 hours to obtain the powder.

[0011] Preferably, the dispersant is any one of ammonium polyacrylate KD-2, polyethylene glycol diacrylate 400 and ethoxylated trimethylolpropane triacrylate.

[0012] Preferably, the aggregate is modified calcium hexaaluminate, and the preparation method is as follows: a mixed powder with a molar ratio of calcium carbonate:aluminum oxide of 1:3 is crushed by a 6000 mesh ultrafine grinder, and mixed in a mixing double cone for 0.5h, the mixture is granulated into 2-5mm particles by a fluidized bed with 0.5 times the weight ratio of propylene glycol as a binder, and then calcined at a high temperature of 1500°C for 2h to obtain the product.

[0013] A method for preparing a quick-drying wear-resistant refractory castable composition comprises the following steps:

[0014] S1. Weigh aggregates according to the weight ratio and add them into a mixer. Add matrix powder and dispersant while stirring. Stir and mix for 30 minutes to obtain mixture 1.

[0015] S2. Add the corresponding pH stabilizer and hardener according to weight proportion to the mixture 1, stir and mix evenly, add the sol binder diluted with water to fully mix the solid and liquid, stir for 5 minutes, and form a casting material with good fluidity.

[0016] Preferably, in step S2, the volume of the sol binder diluted with water is 4 times the volume of the sol binder.

[0017] Beneficial effects: Through the application of sol binder, because the sol binder is previously adsorbed by anion and cation exchange resin to remove other impurities, the impurities introduced are reduced or even eliminated, which can improve the high-temperature performance of the castable, increase the use temperature, and the solidification mechanism of the sol binder will not produce hydration products containing a large amount of bound water. Moreover, after hardening, the castable matrix has high air permeability and porous structure, which reduces the risk of matrix bursting, can be dried quickly and safely, and due to the high surface area of ​​the sol binder particles, the sintering performance of the castable can be improved; the pH stabilizer can reduce the damage of environmental factors to the castable in the later use, and extend the service life; adding a hardener can accelerate hardening, making the castable more wear-resistant. The castable of the present invention has a wider range of applicability, and its preparation method is simple and efficient, which can reduce costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic diagram of the gelation of the silica sol of the present invention.

[0019] Figure 2 It is a schematic diagram of the effect of pH value on the gelation time of silica sol in the present invention. DETAILED DESCRIPTION

[0020] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0021] Example 1

[0022] Preparation of small particle size silica sol:

[0023] Add 0.3 times the volume of strong acid cation exchange resin to 19.6 degrees Baume water glass, stir mechanically for 10 minutes, filter, wash the filtered strong acid cation exchange resin again with 0.5 times the volume of water glass, stir for 5 minutes, filter, combine the two filtrates, add 0.1 times the volume of water glass weak alkaline anion exchange resin, stir for 10 minutes, filter, slurry and stir the filtered weak alkaline anion exchange resin with 0.2 times the volume of water glass, filter, combine all filtrates, adjust pH to 9-10 with 4M sodium hydroxide aqueous solution, concentrate the solution at 80°C under reduced pressure to 1 / 4 of the original volume, add hexadecyltrimethylammonium nitrate in an amount of 1 / 50 of the weight of water glass and nano magnesium oxide in an amount of 1 / 200 of the weight of water glass while stirring, and stir to obtain.

[0024] Preparation of homemade calcium dodecaaluminate nanopowder:

[0025] The mixed powder with a molar ratio of calcium carbonate:aluminum chloride of 12:7 was dissolved in 40°C water of 20 times the weight of the mixture under stirring, and after the solution was clear, ammonia water was added dropwise to adjust the pH to 11-12, and the mixture was naturally cooled and precipitated for 24 hours, filtered, and calcined at high temperature of 1500°C for 2 hours.

[0026] Preparation of modified calcium hexaaluminate:

[0027] The mixed powder with a molar ratio of calcium carbonate to aluminum oxide of 1:3 was crushed by a 6000 mesh superfine grinder and mixed in a mixing double cone for 0.5 h. The mixture was granulated into 2-5 mm particles by a fluidized bed with 0.5 times the weight ratio of propylene glycol as a binder, and then calcined at 1500°C for 2 h to obtain the product.

[0028] S1. Weigh 6 kg of modified calcium hexaaluminate according to the weight ratio and add it into a blender. Add 1.5 kg of homemade calcium heptaaluminate dodecahydrate nanopowder and 0.2 kg of polyethylene glycol diacrylate 400 under stirring, and stir and mix for 30 minutes to obtain a mixture 1.

[0029] S2. Add 0.05 kg of active zinc oxide powder and 0.1 kg of magnesium oxide powder to mixture 1, stir and mix evenly, add 1.5 kg of small-particle silica sol diluted with 6 kg of water to fully mix the solid and liquid, stir for 5 minutes, and form a castable with good fluidity.

[0030] Example 2

[0031] Preparation of small particle size silica sol:

[0032] Add 0.3 times the volume of strong acid cation exchange resin to 19.6 degrees Baume water glass, stir mechanically for 10 minutes, filter, wash the filtered strong acid cation exchange resin again with 0.5 times the volume of water glass, stir for 5 minutes, filter, combine the two filtrates, add 0.1 times the volume of water glass weak alkaline anion exchange resin, stir for 10 minutes, filter, slurry and stir the filtered weak alkaline anion exchange resin with 0.2 times the volume of water glass, filter, combine all filtrates, adjust pH to 9-10 with 4M sodium hydroxide aqueous solution, concentrate the solution at 80°C under reduced pressure to 1 / 4 of the original volume, add hexadecyltrimethylammonium nitrate in an amount of 1 / 50 of the weight of water glass and nano magnesium oxide in an amount of 1 / 200 of the weight of water glass while stirring, and stir to obtain.

[0033] Preparation of homemade calcium dodecaaluminate nanopowder:

[0034] The mixed powder with a molar ratio of calcium carbonate:aluminum chloride of 12:7 was dissolved in 40°C water of 20 times the weight of the mixture under stirring, and after the solution was clear, ammonia water was added dropwise to adjust the pH to 11-12, and the mixture was naturally cooled and precipitated for 24 hours, filtered, and calcined at high temperature of 1500°C for 2 hours.

[0035] Preparation of modified calcium hexaaluminate:

[0036] The mixed powder with a molar ratio of calcium carbonate to aluminum oxide of 1:3 was crushed by a 6000 mesh superfine grinder and mixed in a mixing double cone for 0.5 h. The mixture was granulated into 2-5 mm particles by a fluidized bed with 0.5 times the weight ratio of propylene glycol as a binder, and then calcined at 1500°C for 2 h to obtain the product.

[0037] S1. Weigh 6.5 kg of modified calcium hexaaluminate according to the weight ratio and add it into a blender. Add 2 kg of self-made calcium heptaaluminate dodecahydrate nanopowder and 0.25 kg of polyethylene glycol diacrylate 400 under stirring, and stir and mix for 30 minutes to obtain a mixture 1.

[0038] S2. Add 0.1 kg of active zinc oxide powder and 0.15 kg of magnesium oxide powder to mixture 1, stir and mix evenly, add 2 kg of small-particle silica sol diluted with 8 kg of water to fully mix the solid and liquid, stir for 5 minutes, and form a castable with good fluidity.

[0039] Example 3

[0040] Preparation of small particle size silica sol:

[0041] Add 0.3 times the volume of strong acid cation exchange resin to 19.6 degrees Baume water glass, stir mechanically for 10 minutes, filter, wash the filtered strong acid cation exchange resin again with 0.5 times the volume of water glass, stir for 5 minutes, filter, combine the two filtrates, add 0.1 times the volume of water glass weak alkaline anion exchange resin, stir for 10 minutes, filter, slurry and stir the filtered weak alkaline anion exchange resin with 0.2 times the volume of water glass, filter, combine all filtrates, adjust pH to 9-10 with 4M sodium hydroxide aqueous solution, concentrate the solution at 80°C under reduced pressure to 1 / 4 of the original volume, add hexadecyltrimethylammonium nitrate in an amount of 1 / 50 of the weight of water glass and nano magnesium oxide in an amount of 1 / 200 of the weight of water glass while stirring, and stir to obtain.

[0042] Preparation of homemade calcium dodecaaluminate nanopowder:

[0043] The mixed powder with a molar ratio of calcium carbonate:aluminum chloride of 12:7 was dissolved in 40°C water of 20 times the weight of the mixture under stirring, and after the solution was clear, ammonia water was added dropwise to adjust the pH to 11-12, and the mixture was naturally cooled and precipitated for 24 hours, filtered, and calcined at high temperature of 1500°C for 2 hours.

[0044] Preparation of modified calcium hexaaluminate:

[0045] The mixed powder with a molar ratio of calcium carbonate to aluminum oxide of 1:3 was crushed by a 6000 mesh superfine grinder and mixed in a mixing double cone for 0.5 h. The mixture was granulated into 2-5 mm particles by a fluidized bed with 0.5 times the weight ratio of propylene glycol as a binder, and then calcined at 1500°C for 2 h to obtain the product.

[0046] S1. According to the weight ratio, 7 kg of modified calcium hexaaluminate was weighed and added into a blender. 2.5 kg of self-made calcium heptaaluminate dodecahydrate nanopowder and 0.3 kg of polyethylene glycol diacrylate 400 were added under stirring. The mixture was stirred for 30 min to obtain a mixture 1.

[0047] S2. Add 0.15 kg of active zinc oxide powder and 0.2 kg of magnesium oxide powder to mixture 1, stir and mix evenly, add 2.5 kg of small-particle silica sol diluted with 10 kg of water to fully mix the solid and liquid, stir for 5 minutes, and form a castable with good fluidity.

[0048] Comparative Example 1

[0049] Same as Example 1, except that ordinary silicon powder is used instead of small-particle silica sol.

[0050] Table 1 shows the physical properties of a quick-drying wear-resistant refractory castable composition prepared in the above example.

[0051] Table 1

[0052]

[0053] Through the inspection data, it can be seen that the quick-drying wear-resistant refractory castable composition of Examples 1-3 shows good performance in terms of wear resistance, final setting time, thermal conductivity, compression and flexural strength.

[0054] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A quick-drying wear-resistant refractory castable composition, characterized in that: The composition comprises the following components mixed in parts by weight: 15-25 parts of sol binder, 0.5-1.5 parts of pH stabilizer, 1-2 parts of hardener, 15-25 parts of matrix fine powder, 2-3 parts of dispersant and 60-70 parts of aggregate; The sol binder is a small-particle silica sol, and the preparation method is as follows: add 0.3 times the volume of strong acid cation exchange resin to 19.6 degrees Baume water glass, mechanically stir for 10 minutes, filter, and wash the filtered strong acid cation exchange resin again with 0.5 times the volume of water glass, stir for 5 minutes, filter, combine the two filtrates, add 0.1 times the volume of water glass weak alkaline anion exchange resin, stir for 10 minutes, filter, and slurry and stir the filtered weak alkaline anion exchange resin with 0.2 times the volume of water glass, filter, combine all filtrates, adjust pH to 9-10 with 4M sodium hydroxide aqueous solution, and concentrate the solution at 80°C under reduced pressure to 1 / 4 of the original volume, add hexadecyltrimethylammonium nitrate with 1 / 50 of the weight of water glass and nano magnesium oxide with 1 / 200 of the weight of water glass under stirring, and stir to obtain; The pH stabilizer is active zinc oxide powder, and the particle size of the active zinc oxide powder is 10-30nm; The matrix fine powder is a self-made calcium dodecaaluminate nano powder. The preparation method of the self-made calcium dodecaaluminate nano powder is as follows: dissolve the mixed powder of calcium carbonate and aluminum chloride in 40°C water with a weight of 20 times the weight of the mixture under stirring, add ammonia water to adjust the pH to 11-12 after the mixture is dissolved, cool and precipitate naturally for 24 hours, filter, and calcine at a high temperature of 1500°C for 2 hours to obtain the powder; The aggregate is modified calcium hexaaluminate, and the preparation method is as follows: the mixed powder of calcium carbonate and aluminum oxide is crushed by a 6000 mesh ultrafine grinder, and mixed in a mixing double cone for 0.5h, the mixture is granulated into 2-5mm particles by a fluidized bed with 0.5 times the weight ratio of propylene glycol as a binder, and then calcined at a high temperature of 1500°C for 2h to obtain the aggregate.

2. The quick-drying wear-resistant refractory castable composition according to claim 1, characterized in that: The hardener is magnesium oxide micropowder, and the particle size of the magnesium oxide micropowder is 1-5mm.

3. The quick-drying wear-resistant refractory castable composition according to claim 1, characterized in that: During the preparation of the matrix fine powder, the molar ratio of calcium carbonate:aluminum chloride is 12:

7.

4. The quick-drying wear-resistant refractory castable composition according to claim 1, characterized in that: The dispersant is polyethylene glycol diacrylate 400.

5. The quick-drying wear-resistant refractory castable composition according to claim 1, characterized in that: During the preparation of aggregate, the molar ratio of calcium carbonate:aluminum oxide is 1:

3.

6. A method for preparing the quick-drying wear-resistant and refractory castable composition according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Weigh aggregates according to the weight ratio and add them into a mixer. Add matrix powder and dispersant while stirring. Stir and mix for 30 minutes to obtain mixture 1. S2. Add the corresponding pH stabilizer and hardener according to weight proportion to the mixture 1, stir and mix evenly, add the sol binder diluted with water to fully mix the solid and liquid, stir for 5 minutes, and form a casting material with good fluidity.

7. The method for preparing the quick-drying wear-resistant and refractory castable composition according to claim 6, characterized in that: In step S2, the sol binder diluted with water is stirred, and the volume of the dilution water is 4 times the volume of the sol binder.

Citation Information

Patent Citations

  • Nano-SiO2 and nano-CaO composite ceramic bond siliceous refractory castable and preparation method thereof

    CN101875561A

  • Ceramic filter for continuous casting tundish and method for preparing the same

    CN104944984A